COMMAND SYSTEM FOR MOVEMENT CONTROL DEVELOPMENT (Multidisciplinary Journal of Science and Technology, 2024)
The paper presents research on robot’s command recognition and motion capture. There is developed a command system, which is pre-defined and universal for the motion of a great amount of robots. The system perceives all commands given by the operator as a three-dimensional vector of values. In the process of experiments using machine learning methods, research and classification of signals for each of the commands and states of the robot based on the data received from the sensors was performed. For machine learning of the system, it was decided to use the MatLab program package